2003
DOI: 10.18474/0749-8004-38.4.654
|View full text |Cite
|
Sign up to set email alerts
|

New Source of Southern Chinch Bug (Hemiptera: Lygaeidae) Resistance in a Diploid Selection of St. Augustinegrass

Abstract: Over 400,000 ha of St. Augustinegrass, Stenotaphrum secundatum (Walt.) Kuntze, are managed as a turfgrass in the southern United States, and the southern chinch bug, Blissus insularis Barber, is its most important insect pest. New sources of host plant resistance to southern chinch bugs became necessary due to the development of virulent populations of chinch bugs which were able to feed on the only acceptable resistant cultivar, Floratam. Initial testing evaluated 14 lines for chinch bug resistance using inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…The most notable of the recovered progeny had African polyploid genotypes as maternal parents. For example, FX-10 is a cultivar derived from African polyploid germplasm known to possess genes conferring the most stable form of resistance to chinch bug (Busey 2003;Nagata and Cherry 2003). Future breeding efforts should focus on crossing these exotic genetic resources with superior diploid cultivars to improve sod production, cold hardiness, color, texture, shade tolerance, and marketable turf quality in St. Augustinegrass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most notable of the recovered progeny had African polyploid genotypes as maternal parents. For example, FX-10 is a cultivar derived from African polyploid germplasm known to possess genes conferring the most stable form of resistance to chinch bug (Busey 2003;Nagata and Cherry 2003). Future breeding efforts should focus on crossing these exotic genetic resources with superior diploid cultivars to improve sod production, cold hardiness, color, texture, shade tolerance, and marketable turf quality in St. Augustinegrass.…”
Section: Discussionmentioning
confidence: 99%
“…Floratam was the industry standard for chinch bug resistance until being rendered obsolete by the polyploid-damaging population (PDP) biotype of the pest (Busey 2003). With the identification of a diploid cultivar (NUF-76 also known as 'Captiva') possessing resistance to the PDP chinch bug (Nagata and Cherry 2003), it is technically feasible to stack resistance genes by crossing Floratam or FX-10 with NUF-76. Turf quality characteristics of NUF-76, however, are unknown and warrant evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Floratam, a polyploid variety of St. Augustinegrass with resistance to southern chinch bug, was released in Florida and other Gulf Coast states in 1973 (Horn et al 1973). However, in 1985, a population of chinch bug in Florida was reported to have overcome Floratam's resistance (Busey and Center 1987); this ability to use Floratam as a host is now widespread throughout Florida (Nagata and Cherry 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As potential alternatives to Floratam, two southern chinch bug resistant St. Augustinegrass varieties were developed: a polyploid line, FX-10 (Busey 1993) and a diploid line, Captiva (Nagata and Cherry 2003). We have shown that both FX-10 and Captiva deter feeding of southern chinch bugs (i.e., through antixenosis) (Rangasamy et al 2006).…”
Section: Introductionmentioning
confidence: 99%